The South African Commercial Advertiser and the Eastern Frontier, 1834-1847: an examination of the ways in which and the sources from which it reported frontier conflicts - Frye, John (Rhodes University, Faculty of Humanities, Department of History, 1968)
[From Introduction]. The name of John Fairbairn is remembered with honour in South Africa for the part he played in the achievement of a freer press in the Cape Colony, in the campaign to prevent Britain from establishing a convict station on Cape soil, and in the movement which resulted in the establishment of a form of representative government in the Cape in 1853. More controversial is his share, as the editor of the first modern newspaper in the Colony, in a campaign to secure just treatment for the natives both inside and outside of the Colony. It is with his treatment of the conflicts, both small and great, between the Colony and the AmaXhosa tribes on its Eastern Frontier that this study is concerned.
Keywords: Fairbairn, John, 1794-1864; South African Commercial Advertiser (Newspaper); South Africa -- History -- Frontier Wars, 1811-1878